Complexity reduction algorithm for prediction unit decision process in high efficiency video coding. Issue 1 (1st January 2016) - Lee, Jong‐Hyeok; Kim, Byung‐Gyu; Jun, Dong‐San; Jung, Soon‐Heung; Choi, Jin Soo
Abstract : To provide very high quality and/or high resolution video content under limited bandwidth conditions for transmission or storage, the high efficiency video coding (HEVC) has been recently finalised by the joint collaborative team on video coding. In this study, the authors propose a fast prediction unit (PU) decision method to reduce the computational complexity of HEVC encoder. They use an early PU decision in each coding unit‐level based on spatio‐temporal analyses and depth correlations. They also consider a classification of motion activity. Experimental results show that the encoding complexity can be reduced by up to 38% on average in the random access main profile configuration with only a small bit‐rate increment and a peak signal to noise ratio (PSNR) decrement, compared to high efficiency video coding test model (HM) 7.0 reference software.